Development of a Colloidal Gold-Based Immunochromatographic Strip for Rapid Detection of H7N9 Influenza Viruses - Sun, Zhihao; Shi, Baolan; Meng, Feifei; Ma, Ruonan; Hu, Qingyun; Qin, Tao; Chen, Sujuan; Peng, Daxin; Liu, Xiufan (Frontiers in Microbiology, 2018)
Both highly and low pathogenic H7N9 influenza A virus (IAV) infections have been found in human and poultry in China, and most human cases were related to contacting infected poultry. It is necessary to develop a rapid, simple method to detect H7N9 IAV from infected poultry. In this study, 13 monoclonal antibodies (McAbs) against hemagglutinin of H7N9 IAV were developed, and three critical amino acid epitopes (198, 227, 235) were identified basing on the reactivity of these variant and wild-type strains with the McAbs. After optimizing the combination among the three McAbs, we developed an immunochromatographic assay for H7N9 AIVs using two McAbs recognized the epitope position 227 and 235. The developed strip had good specificity, stability and sensitivity, the detection limit of swab and tissue samples was 2.5 log10EID50/0.1mL, which is applicable to the clinical samples. This assay provided an effective method for the rapid detection of H7N9 AIVs in the poultry.